Prevalence and risk factors of anaemia among pregnant women in eastern Nepal - Sinha, Amar Kumar; Singh Karki, Gyanendra Man; Karna, Keshab Kumar; Gaire, Chandra Prakash (Journal of Chitwan Medical College, 2018)
Anaemia is the commonest problem in pregnancy throughout the world and vast majority of this burden occurs in developing countries especially in Nepal. The study was aimed for determining the various risk factors of anaemia in group of pregnant women of eastern region located in Nepal. To assess prevalence of anaemia and to identify the association between the demographic variables of pregnant women of eastern region. Thus there is necessity for investigate the prevalence of anaemia for pregnant women. This was a follow-up study design was for the study in Obstetrics and Gynaecology department, Birat Medical College & Teaching Hospital, Biratnagar conducted from Oct. 2014 to Jan. 2016.A total of 545 pregnant women were enrolled in this study. Venous blood was obtained for determination of haemoglobin and questionnaire was designed to collect age of marriage, age of first child birth and socioeconomic status. Women were followed up at delivery. Haemoglobin levels of 10-10.9 g/dl, 7.0-9.9 g/dl and